(untitled) (IUBAT Review, 2025)
This review examines the influence of English proficiency on financial stability and career advancement by synthesizing findings from 52 peer-reviewed studies published between 2000 and 2024. Drawing from literature across linguistics, economics, and education, the paper explores how English language skills affect income levels, job opportunities, career mobility, and the challenges posed by linguistic barriers. Through a comprehensive review of recent literature, the study highlights a strong correlation between English proficiency and economic empowerment, particularly in globalized labor markets. It also discusses effective strategies to enhance language skills, including contextualized language programs, technological interventions, workplace training, and policy initiatives. A key research gap identified is the limited availability of longitudinal studies that establish causality between English proficiency and long-term economic outcomes, especially in developing countries. This review contributes a multidimensional perspective by connecting language ability with socioeconomic equity and recommending holistic, policy-driven approaches for fostering linguistic inclusion and economic integration. IUBAT Review—A Multidisciplinary Academic Journal, 8(1): 258-274